ANALISIS PROSES PEMERIKSAAN BANDING PADA PENGADILAN TINGGI MILITER MEDAN - Marolop Butar Butar; Jogi Handroko Butar Butar; Nathaniel Giovanni Butar Butar (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: The main military law in Indonesia is currently regulated in Law No. 3 of 2025 (replacing Law 34/2004) concerning the Indonesian National Armed Forces (TNI), which regulates the duties, functions, and retirement age of soldiers. Furthermore, Law No. 25 of 2014 governs military disciplinary law, whereas Law No. 31 of 1997 regulates the military court system. Military courts function as institutions that exercise judicial authority within the armed forces to enforce law and justice while considering the interests of national defense and security. The bodies included in the scope of military justice are those that exercise judicial power within the military justice system, which includes the Military Court, the High Military Court, the Supreme Military Court, and the Combat Military Court. The implementation of these military regulations aims to ensure the supremacy of civilian authority within a democratic system, while maintaining the discipline and professionalism of the TNI as an instrument of national defense. Keywords: Military Law, Military Court, TNI   Abstrak: Undang-Undang (UU) Militer di Indonesia yang utama saat ini diatur dalam UU No.3 Tahun 2025 (menggantikan UU 34/2004) tentang Tentara Nasional Indonesia (TNI), yang mengatur tugas, fungsi, dan usia pensiun prajurit. Selain itu UU No.25 Tahun 2014 mengatur hukum disiplin militer, serta UU No. 31 Tahun 1997 mengatur peradilan militer. Peradilan militer merupakan institusi yang melaksanakan kewenangan kehakiman di lingkungan angkatan bersenjata guna menegakkan hukum dan mewujudkan keadilan, dengan tetap mempertimbangkan kepentingan pertahanan serta keamanan negara. Dalam pelaksanaannya, peradilan militer mencakup beberapa badan peradilan yang memiliki fungsi kehakiman, yaitu Pengadilan Militer, Pengadilan Militer Tinggi, Pengadilan Militer Utama, dan Pengadilan Militer Pertempuran. Implementasi peraturan Militer ini untuk memastikan supremasi sipil dalam demokrasi, sekaligus mempertahankan kedisiplinan dan profesionalisme TNI sebagai alat pertahanan negara. Kata kunci: Undang-Undang Militer, Peradilan Militer, TNI